Accounting Information Systems and Decision-Making - Granlund Markus; Teittinen Henri (Routledge, 2023)
In this chapter, we outline how modern accounting information systems (AIS) can support managerial decision making in contemporary organisations. We also outline some future trends regarding this topic. We start by describing the factors constituting different decision-making environments and what we call data environments. This lays a foundation for describing what kind of information is needed in different contexts and how AIS can support managers in making informed decisions. We analyse the topic with four examples: pricing decisions, product mix decisions, equipment replacement investments, and outsourcing decisions. In order to be able to make justified decisions, managers need something to build their decisions on. During the last decade, the idea of fact-based decision making has gained more momentum. This means that decisions could and should be based more on ‘cold facts’ instead of intuition, beliefs, and feelings. This development is supported by recent developments in information and communications technology (ICT), such as big data and business analytics. The need for more and better information derives from the complexity and dynamics of the global markets and its implications for ‘success recipes’. In brief, the whole existence of modern ICT and AIS therein is based on information needs.
The Routledge Handbook of Accounting Information Systems